Technological entrepreneurship readiness - Takawira Ndofirepi; Renier Steyn (Journal of BRICS Studies)
Technological entrepreneurship presents opportunities for accelerated growth during the Fourth Industrial Revolution and assessing the readiness for such entrepreneurship would be important to investors (interested in profit) and governments (interested in economic growth).  The aim was to assess and rank the BRICS (Brazil, Russia, India, China, and South Africa) countries on their level of technological entrepreneurship readiness, as to direct investor funding or alternatively guide government initiatives. Data which was collected in Brazil, Russia, India, China, and South Africa, for the World Values Survey, was used in the study (N=13 895). Mean and composite scores linked to entrepreneurship as well as the embracement of technology were compared across countries. These were combined to generate a score used to rank the countries. With each of the individual, as well as the composite variables, significant differences were found across the BRICS countries. China was rated the highest on attitudes towards science while South Africa was rated highest on the openness to entrepreneurship. On the composite score, technology entrepreneurship readiness, China scored the highest. China was ranked as the BRICS countries most viable for technology entrepreneurship. Technology investors should thus consider directing their venture capital eastward. The governments of the other countries should take note of their shortcomings and the results could inform policies to enhance readiness. The results, at a theoretical level, provided some insights into the conceptualisation of technology-related entrepreneurship.